Knowledge of biosecurity measures among health personnel - Ruiz de Somocurcio Bertocchi, Jorge A. (2017)
Objective: To determine the level of knowledge of biosecurity measures among the professional personnel of the Hospital Nacional Hipólito Unanue (HNHU), to quantify the workers in groups by different features, and to analytically compare their frequencies and percentages, in order to recognize the most vulnerable groups and focus on them on future trainings. Materials and methods: This observational, analytical and cross-sectional study included all professional health personnel of the HNHU who agreed to answer the assessment questionnaire. A sample of 567 workers was obtained, with an acceptable margin of error of 3.32%, a confidence level of 99% and a population behavior of 50%. A questionnairetype form with a total of 10 questions related to biosecurity measures was used as tool for collecting information, which was submitted and distributed by the head of each HNHU service. Data were analyzed according to their frequencies, percentages and the non-parametric chi square test. Results: Twenty-one percent (21%) of the evaluated personnel had a score of 8 to 10 correct answers, 75% of 4 to 7, and 4% of 0 to 3. There were significant differences in the level of knowledge based on variables, such as occupational group, age, tenure at the hospital, gender by occupational group, gender by age, and induction training. Conclusions: Knowledge of biosecurity measures among the hospital's professional personnel is not the ideal one, leading to high biological risk for both the professional and technical personnel and the patients. It is possible to provide training on biosecurity focused on the most vulnerable groups, and to improve its quality and impact.